(untitled) (Iranian Journal of Kidney Diseases, 2010)
Depression and anxiety are among the most common comorbid illnesses in people with end-stage renal disease (ESRD). Patients with ESRD face many challenges which increase the likelihood that they will develop depression or anxiety or worsen these conditions. These include a general feeling of unwellness; specific symptoms caused by ESRD or the patient’s treatment; major disruptions in lifestyle; the need to comply with treatment regimens, including dialysis schedules, diet prescription, and water restriction; ancillary treatments and hospitalizations; and the fear of disability, morbidity, and shortened lifespan. Depression has been studied extensively in patients on maintenance dialysis, and much effort has been done to validate the proper screening tools to diagnose depression and to define the treatment options for patients on maintenance dialysis with depression. Anxiety is less well studied in this population of patients. Evidence indicates that anxiety is also common in maintenance dialysis. More attention should be paid to measuring the incidence and prevalence and developing methods of diagnosis and treatment approaches for anxiety in patients with ESRD. In this review, we attempted to underscore those aspects of depression and anxiety that have not been investigated extensively, especially with regard to anxiety. The interaction between racial/ethnic characteristics of patients on maintenance dialysis with depression and anxiety needs to be studied more extensively, in order to assess better approaches to healthcare for these individuals.